2017
DOI: 10.3390/coatings7120224
|View full text |Cite
|
Sign up to set email alerts
|

Modified Starch-Chitosan Edible Films: Physicochemical and Mechanical Characterization

Abstract: Starch and chitosan are widely used for preparation of edible films that are of great interest in food preservation. This work was aimed to analyze the relationship between structural and physical properties of edible films based on a mixture of chitosan and modified starches. In addition, films were tested for antimicrobial activity against Listeria innocua. Films were prepared by the casting method using chitosan (CT), waxy (WS), oxidized (OS) and acetylated (AS) corn starches and their mixtures. The CT-star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…A comparison study focusing on the main and physical features of chitosan and altered starches of edible films was examined by Garcia et al [ 67 ]. The films’ arrangement was made using a casting strategy that utilises chitosan, waxy, oxidized, and acetylated corn, and their respective blends.…”
Section: Starch As a Biodegradable Packaging Materialsmentioning
confidence: 99%
“…A comparison study focusing on the main and physical features of chitosan and altered starches of edible films was examined by Garcia et al [ 67 ]. The films’ arrangement was made using a casting strategy that utilises chitosan, waxy, oxidized, and acetylated corn, and their respective blends.…”
Section: Starch As a Biodegradable Packaging Materialsmentioning
confidence: 99%
“…Starch is the most abundant and commonly used renewable, biodegradable natural resource, with recognized flexibility, transparency, and film-forming ability, but with low mechanical and barrier properties that are usually improved by mixing the starch with other polymers (e.g., chitosan) [168]. For example, previous studies have reported that the chitosan-starch blends exhibited an improved barrier and mechanical properties as well as good antimicrobial effect [169,170]. Alginate is a naturally occurring polysaccharide can be used in coating for extending the shelf-life of fruit, vegetable, meat, poultry, and film preparation [171].…”
Section: Chitosan/starch/alginate Containing Plant Extracts As Ediblementioning
confidence: 99%
“…However, previous investigations such as influence of drying on barrier and strength properties were mostly performed using casted freestanding films. Furthermore, the cellulosic fibre based substrates that have been used for coating are laboratory-produced paper sheets, which serve as a model for possible industrial applications [29,30,31]. The results of already published work represent valuable basis for further development and practical applications of chitosan in surface treatment of fibre based packaging material presented in our work.…”
Section: Introductionmentioning
confidence: 98%